Organizational change in international bureaucracies - Bauer, M. W.; Jörgens, H.; Knill, C. (The management of UN peacekeeping: coordination, learning, and leadership in peace operations, 2017)
International organizations are important participants in the realm of world politics. An area in which this has become highly visible is the field of United Nations peace operations. Since the end of the Cold War, UN peace operations have increased in number, geographical focus, as well as in their overall complexity.